A Case Study On Factors Influencing Credit Card Usage - Suhana, Mohamed; Norsuridah, Shahdon; Rohana, Sham; Nooririnah, Omar; Aznilinda, Zainuddin; Raja Zuraidah, Raja Mohd Rasi (TextRoad Publication, 2016)
Credit cards have become a necessity to the public and the number of credit cards approved has increased recently. Due to that factor, it had led to the increment of credit card debts. While some of the credit card holders used it wisely, most of them struggled to pay the minimum balance every month. Therefore, it is time to look into this matter. Thus, the objective of this study is to find the correlation between influencing factors and the credit card debts among KLM private hospital staff. The study used convenience sampling and the survey was conducted among 120 credit card holders in the KLM private hospital staff. It is found that only credit related knowledge is significant and has positive influence to the credit card debts. In conclusion, Malaysian government should tighten the guideline of approving credit card by a commercial bank. The aggressive promotion by commercial banks should be controlled and the continuous education on the impact of credit card debt to Malaysian should be done regularly. Commercial banks must play their role in advising the credit card holders on the advantages and the disadvantages of using the credit cards.